IMAGE OF THE INTERNAL REVENUE SERVICE. - Brighton, Gerald D. (The Accounting Review, 1964)
The article focuses on the study of Internal Revenue Services in accounting courses. In teaching accounting courses, field trips are not often used. Probably only for special situations and for relatively small groups could they be effective. In its graduate course in income tax at the University of Illinois, "Income Tax Development," one of the university's objectives is to give students some comprehension of current developments, including tax practice and relationships between practitioners and the Internal Revenue Service. In studying the Internal Revenue Service the university has some formal reading assignments. Whenever schedules will permit the university will try to culminate this with an all-day visit to a District Office of the lnternal Revenue Service. It has been extremely interesting to observe reactions of students to this visit. It is clear that the purpose of the paper is not simply to discuss the image of the Internal Revenue Service. This is an interesting subject in itself, but is intended as an illustration of the image of almost any government servant. The author feels that better understanding on the part of the enlightened public is needed, and will lead to better service and better rewards for service.